MAPK pathway in melanoma part II—secondary and adaptive resistance mechanisms to BRAF inhibition. (March 2017) - Amaral, Teresa; Sinnberg, Tobias; Meier, Friedegund; Krepler, Clemens; Levesque, Mitchell; Niessner, Heike; Garbe, Claus
Abstract: BRAF mutation can be identified in about 45% of the patients with metastatic melanoma. In these patients, BRAF and MEK inhibitors are able to induce rapid responses and to prolong survival. However, a significant percentage of patients will develop resistance to targeted therapy and will have progressive disease. MAPK pathway is the most important pathway involved in BRAF/MEK inhibition resistance, particularly MAPK pathway reactivation. Resistance mechanisms can be classified as 1) primary or intrinsic characterised by no response to therapy, 2) secondary or acquired with MAPK pathway reactivation after a time of tumour regression and 3) as adaptive with initial response and early resistance. BRAF inhibition also alters the immune response. Several publications have described immune effects of BRAF inhibition in melanoma tumours, showing that combining targeted and immunotherapy can improve response, despite a possible cross-resistance. Here, we continue the review on resistance mechanisms to BRAF/MEK inhibition and focus on the secondary and adaptive mechanisms. Highlights: Resistance to BRAF inhibition (BRAFi) therapy leads to progressive disease. Secondary BRAFi resistance occurs with MAPK reactivation after an initial response. Adaptive BRAFi resistance is associated with initial response and early resistance. BRAFi also alters immune response with possible implications in sequencing therapy.